Shadow pandemic: domestic violence and child abuse during the covid-19 lockdown in India - Ravichandran, Prabhadevi; Shah, Anuradha Kunal; Ravichandran, Prabhu (International Journal of Research in Medical Sciences, 2020)
For many women and children around the world, staying at home is no longer a safety aspect during the Covid-19 pandemic. There is a surge in the number of cases of inter-personal violence and child abuse during the lockdown. The stigma and socio-cultural norms create hesitance in subjecting the family and its intimate relationships to public scrutiny. Therefore, building awareness around domestic violence is vital.